Pengaruh motivasi belajar dan kerukunan teman sebaya terhadap prestasi belajar siswa kelas atas di SD Muhammadiyah 16 Karangasem Tahun 2015/2016 - Susanti, Okta Prasetyani (2016)
This study aims to determine: (1) the effect of learning motivation on student achievement upscale, (2) the effect of harmony peers on student achievement upscale, and (3) the effect of learning motivation and harmony peers on student achievement upscale. This research uses quantitative and design Ex-Posfacto research. The object of this study is upscale students (IV, V, VI) which total number is 325 students of SD Muhammadiyah 16 Karangasem. A sample of 81 students is by using proportionate stratified random sampling. The data analysis method that uses multiple regression prerequisite test in the form of normality and linearity test. Based on the analysis results obtained multiple regression equation: Y = 53.750 + 0.184 X1 + 0.174 X2. The results of this study indicate that: (1) there is learning motivation on learning achievement upscale to obtain tcount 2,343> 1,990 ttable, and the effective contribution is 17.9088%. (2) there is positive and significant harmony peers on student achievement upscale to obtain tcount 2,650> 1,990 ttable, and the effective contribution is 20.592%. (3) there is motivation to learn and harmony peers on student achievement upscale to obtain the value of F 24.412> F table 3.15, the effective contribution of learning motivation and harmony friend peer together the learning achievement is 38.5% and the remaining 61.5% is influenced by other factors. Based on the results of this study,it can be concluded that there are the effect significant of learning motivation and harmony peers on learning achievement upscale in SD Muhammadiyah 16 Karangasem in 2015/2016. Keywords: learning motivation, harmony peers, and learning achievement